The Korean Study of Women's Health-Related Issues (K-Stori): Rationale and Study Design - Ha Na Cho; Eunji Choi; Da Hea Seo; Mina Suh; Hoo-Yeon Lee; Boyoung Park; Sohee Park; Juhee Cho; Sue Kim; Yeong-Ran Park; Joong-Yeon Lim; Younjihin Ahn; et al. (BMC, 2017)
Abstract Background Measures to address gender-specific health issues are essential due to fundamental, biological differences between the sexes. Studies have increasingly stressed the importance of customizing approaches directed at women's health issues according to stages in the female life cycle. In Korea, however, gender-specific studies on issues affecting Korean women in relation to stages in their life cycle are lacking. Accordingly, the Korean Study of Women's Health-Related Issues (K-Stori) was designed to investigate life cycle-specific health issues among women, covering health status, awareness, and risk perceptions. Methods K-Stori was conducted as a nationwide cross-sectional survey targeting Korean women aged 14-79 years. Per each stage in the female life cycle (adolescence, childbearing age, pregnancy & postpartum, menopause, and older adult stage), 3000 women (total 15,000) were recruited by stratified multistage random sampling for geographic area based on the 2010 Resident Registration Population in Korea. Specialized questionnaires per each stage (total of five) were developed in consultation with multidisciplinary experts and by reflecting upon current interests into health among the general population of women in Korea. This survey was conducted from April 1 to June 31, 2016, at which time investigators from a professional research agency went door-to-door to recruit residents and conducted in-person interviews. Discussion The study's findings may help with elucidating health issues and unmet needs specific to each stage in the life cycle of Korean women that have yet to be identified in present surveys.